2015
DOI: 10.1038/ncomms6853
|View full text |Cite
|
Sign up to set email alerts
|

DNase II-dependent DNA digestion is required for DNA sensing by TLR9

Abstract: DNase II digests DNA in endolysosomes. In the absence of DNase II, undigested DNA activates cytoplasmic DNA-sensing pathways. Little is known, however, about the role of DNase II in endolysosomal DNA sensing by TLR9. Here we show that DNase II is required for TLR9. We test two types of TLR9 ligands, CpG-A and CpG-B, and show that only CpG-A response is impaired in DNase II-deficient dendritic cells (DCs). Enzymatically inactive DNase II mutants cannot rescue CpG-A responses. DNase II cleaves CpG-A from 20-mer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 28 publications
3
85
0
Order By: Relevance
“…Noteworthy, it has been shown that inflammasome activation by shorter DNA fragments was stronger than by longer fragments (Dombrowski et al, 2011). Also, the DNase IImediated digestion of genomic DNA into short oligonucleotides is required for endosomal sensing by TLR9 (Chan et al, 2015). Furthermore, in support of an important role for DNA processing in the regulation of immune responses, it has been reported that a lack of DNA degradation by the caspase-activated DNase (CAD), which is responsible for the cell-…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 97%
“…Noteworthy, it has been shown that inflammasome activation by shorter DNA fragments was stronger than by longer fragments (Dombrowski et al, 2011). Also, the DNase IImediated digestion of genomic DNA into short oligonucleotides is required for endosomal sensing by TLR9 (Chan et al, 2015). Furthermore, in support of an important role for DNA processing in the regulation of immune responses, it has been reported that a lack of DNA degradation by the caspase-activated DNase (CAD), which is responsible for the cell-…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 97%
“…In pDCs, the ODNs induce secretion of TNF-a and IL-12. The synthesis of type I IFNs is primarily linked to the A class ODNs (10,20,21), because of the different cellular internalization pathway (25). The B class ODNs captured to nanobeads or cationic lipids trigger IFN-a synthesis in pDCs (32,33), which implies that the propensity of ODNs to internalize into early endosomes, rather than DNA sequence itself, drives MyD88/IRF7-dependent signaling and the IFN-a synthesis (34).…”
Section: Discussionmentioning
confidence: 99%
“…After processing dsDNA with endosomal DNAse II shorter fragments of ssDNA are generated, which than may serve as TLR9 ligands (25). To prevent the degradation of ODNs by nucleases, synthetic ODNs may consist of a partial or complete PTO backbone.…”
Section: Response Of Mouse Dcs To the Minm Odnmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, TLR8 might also sense bacterial RNA degradation products. The concept of recognition of RNA degradation products by TLR8 raises the hypothesis that phosphatases and/or nucleases of bacterial or host origin might play a role upstream of TLR8 activation (45), in analogy to the requirement for lysosomal endonuclease DNase II for the activation of TLR9 (46,47).…”
Section: Tatjana Eigenbrod and Alexander H Dalpkementioning
confidence: 99%